Dari Diam Menjadi Aksi: Meningkatkan Kesadaran dan Mengakhiri Kekerasan dalam Rumah Tangga Melalui Pendidikan Publik - Aristya Windiana Pamuncak; Amsari Damanik; Agustina Wati; Sulung Nugroho; Erna Susanti; Nur Arifudin; Sofwan Rizko Ramadoni; Grizelda Grizelda; Reza Pramasta Gegana (I-Com: Indonesian Community Journal, 2024)
ABSTRACT To prevent and overcome domestic violence, a comprehensive approach is needed that involves various aspects, such as law enforcement, public education, psychological support, and cultural considerations. The problem of partners in this community service activity is the lack of public knowledge about domestic violence and how to handle it. Public education aims to increase public awareness of individual rights, the negative impacts of domestic violence, and the stages of handling it. The method of legal counselling / public Education to partners in this community service activity uses lectures, discussions, questions and answers. Partners participate in this activity by providing time and place and presenting their members as participants in legal counseling to raise public awareness of the dangers of domestic violence. The many questions about the cases experienced indicate an increase in awareness to involve law enforcement, which is a positive step toward overcoming domestic violence. With this legal counseling, a safer family environment is hoped to be created. The community needs a more comprehensive and sustainable support system. Keywords: Domestic Violence, Public Education, Law Enforcement, Legal Counseling.